2014
DOI: 10.1186/1471-244x-14-124
|View full text |Cite
|
Sign up to set email alerts
|

Non-professional-help-seeking among young people with depression: a qualitative study

Abstract: BackgroundAdolescents and young adults often suffer from depression, but tend to avoid seeking professional help. The aim of this study was to explore the reasons for non-professional-help-seeking in a sample of young adults resident in Catalonia with depressive symptoms through a qualitative study. In addition, the subjects were invited to offer their recommendations for making mental health care services more accessible.MethodsWe recruited 105 young persons (17–21 years of age) who had participated in a nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 31 publications
(42 reference statements)
5
54
0
1
Order By: Relevance
“…The identified gender differences may partly reflect masculine norms, including reliance on one's own strengths and resources (79). Thus, by challenging stereotypes and reducing perceived, use of social media to normalize utilization of professional services may help narrow the gender gap in service use and encourage young men to seek professional help (80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identified gender differences may partly reflect masculine norms, including reliance on one's own strengths and resources (79). Thus, by challenging stereotypes and reducing perceived, use of social media to normalize utilization of professional services may help narrow the gender gap in service use and encourage young men to seek professional help (80).…”
Section: Discussionmentioning
confidence: 99%
“…Mental health professionals should consider the specific demands, preferences, and needs of young adults, especially those from potentially vulnerable subgroups, when providing care. This includes their preference for personalized and age-appropriate services and flexible interpersonal communication styles (80,81). Clinicians must be specifically trained in cultural sensitivity and competence to increase intake, retention, and successful treatment of individuals from racial-ethnic minority groups and other vulnerable young clients (24,82).…”
Section: Discussionmentioning
confidence: 99%
“…The study population was relatively young with a median age of 23 years, this is largely from the fact that these images were from the electronic medical records of a tele-health platform for which studies have always related young age with uptake and usage of digital platforms for medical care [22,23]. This further creates an opportunity to leverage on AI applications for dermatological medical care among the young people who often do not have enough resources and rely on peer to peer consultations when managing skin problems a trend seen with other medical problems like mental, sexual and reproductive health [24].…”
Section: Discussionmentioning
confidence: 99%
“…There has been speculation in the scientific literature about this being related to masculine role socialisation (Courtenay, 2000) which thwarts the acquisition of skills, by men, in expressing or in recognising their emotions (Ridge, Emslie, & White, 2011). In extreme cases, this can result in total dissociation from one's emotional worldwhat Levant (1998) has termed normative male alexithymia. However, more recently, research has demonstrated that the lower incidence rate of depression in men may be due to depressed men's inhibitions in disclosing their condition, as a function of their perception of others' reactions to their disclosure (Galasi ski, 2008;Gough, 2016).…”
Section: Atypical Symptoms Of Depressionmentioning
confidence: 99%